The value of high school graduation in the United States: Per-person shadow price estimates for use in cost-benefit analysis - Aidan R. Vining; David L. Weimer (Administrative Sciences, 2019)
One way for jurisdictions with limited analytic resources to increase their capability for doing cost-benefit analysis (CBA) is to use existing shadow prices, or "plug-ins", for important social impacts. This article contributes to the further development of one important shadow price: the value of an additional high school graduation in the United States. Specifically, how valuable to a student, government, and the rest of society in aggregate is a high school graduation? The analysis builds on the method developed by the Washington State Institute for Public Policy and presents numerical updates and extensions to their analysis. For the U.S., the estimated net present value (the social value) using a 3 percent real discount rate of this shadow price is approximately 300,000 per each additional graduate. In appropriate circumstances, this value can be "plugged-in" to CBAs of policies that either directly or indirectly seeks to increase the number of students who graduate from high school.
Keywords: 350; cost-benefit analysis; high-school graduation; shadow price; social value of education; plug-in value